2010
DOI: 10.1210/jc.2010-0917
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of Adults with Congenital Adrenal Hyperplasia: A Cohort Study of 203 Patients

Abstract: Context: No consensus exists for management of adults with congenital adrenal hyperplasia (CAH) due to a paucity of data from cohorts of meaningful size.Objective: Our objective was to establish the health status of adults with CAH.Design and Setting: We conducted a prospective cross-sectional study of adults with CAH attending specialized endocrine centers across the United Kingdom.Patients: Participants included 203 CAH patients (199 with 21-hydroxylase deficiency): 138 women, 65 men, median age 34 (range 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
503
8
24

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 444 publications
(599 citation statements)
references
References 39 publications
39
503
8
24
Order By: Relevance
“…Many studies have demonstrated elevated BMI (9,15,16,20,23) in adults with CAH. Measurement of body composition using DXA has previously demonstrated increased fat mass in young adults with CAH (15, 16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated elevated BMI (9,15,16,20,23) in adults with CAH. Measurement of body composition using DXA has previously demonstrated increased fat mass in young adults with CAH (15, 16).…”
Section: Discussionmentioning
confidence: 99%
“…Our patients had increased insulin release during the OGTT and older patients tended to have higher HbA1c than younger ones, suggesting an increased risk of T2DM in the older CAH males. Insulin resistance has been found in adult CAH by all investigators (6,8,9,12,13,18,(20)(21)(22)(23), but one (18) and has most commonly been expressed as homeostasis model assessment (HOMA) index. We did not calculate this index because fasting glucose was low in our patients, which may lead to a falsely low estimation of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Surgical interventions may sometimes be necessary to tackle elevated gonadal cancer risks or urinary issues. 16,36 These surgical interventions should not be contentious, but firm supporting data are lacking.…”
Section: Medicalisationmentioning
confidence: 99%
“…The importance of ensuring transitional care is highlighted, especially for CAH -see the paper by Arlt in the adrenal Yearbook chapter [4] -as many adults are not under follow-up. There are many adverse health outcomes in CAH when good surveillance is lacking.…”
Section: Testicular Adrenal Rest Tumors In Boys Adolescents and Adulmentioning
confidence: 99%